2009
DOI: 10.1111/j.1601-5223.1970.tb02291.x
|View full text |Cite
|
Sign up to set email alerts
|

Mosaicism for translocation heterozygosity in a malformed pig

Abstract: The chromosome conditions of a malformed and stillborn piglet are described. The animal was a chromosomal mosaic with two clones, one with the normal chromosome complement and one with a reciprocal translocation. The translocation had taken place between the longest chromosome and one of the smallest metacentric ones. The significance of the mosaicism for the malformation of the animal is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…According to our observations, mosaicism for balanced reciprocal chromosome translocation are underreported in the domestic pig. To date only 4 mosaic reciprocal chromosome translocations have been documented in the domestic pig 2,3 , in contrast to the over 200 total constitutional chromosomal rearrangements reported in the literature 1 . In this study we report a total of 39 mosaic chromosome translocations identified in the domestic pig through which we attempt to estimate the prevalence, possible tissue distribution, and interrogate the possible adverse biological effects of somatic chromosome mosaicism in this species.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…According to our observations, mosaicism for balanced reciprocal chromosome translocation are underreported in the domestic pig. To date only 4 mosaic reciprocal chromosome translocations have been documented in the domestic pig 2,3 , in contrast to the over 200 total constitutional chromosomal rearrangements reported in the literature 1 . In this study we report a total of 39 mosaic chromosome translocations identified in the domestic pig through which we attempt to estimate the prevalence, possible tissue distribution, and interrogate the possible adverse biological effects of somatic chromosome mosaicism in this species.…”
Section: Discussionmentioning
confidence: 92%
“…Thus far, only four documented mosaic abnormalities in the domestic pig have been identified through investigation of specific boars. The first reported mosaic translocation for the domestic pig was a mos t (1;11), identified in a malformed stillborn piglet 2 . The other three mosaic translocations, a mos t(7;9), a mos t (7;18), and a mos t (9;18), were proposed to occur recurrently in 13 otherwise healthy pigs as a result of illegitimate recombination between the four genes that make up the porcine T-cell receptor (TCR) 3 .…”
mentioning
confidence: 99%
“…Preparations were also made from bone marrow and from testes. Orcein squash preparations were made according to HANSEN-MELANDER and MELANDER (1969) and SOMLEV et al (1970). The procedures used for Giemsa-band staining are described by HANSEN-MELANDER et al (1974).…”
Section: Methodsmentioning
confidence: 99%